Perancangan Sistem Monitoring Tanda Vital Pada Tubuh Manusia Secara Real Time Dengan Tampilan Desktop - Ariq Monetra; Mochammad Hannats Hanafi Ichsan; Rizal Maulana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The Vital Sign monitoring design is a medical technology system that will be designed to measure 4 Vital Signs in the human body, namely body temperature, heart rate, blood pressure, and oxygen saturation level in the blood, then send the data obtained using the LoRa module and make classification decisions using J48 Decision Tree. This Vital Sign monitoring design is designed because in general medical services still use traditional methods such as measuring blood pressure manually and then writing it on paper. The focus of this research is to get the value of 4 Vital Signs, send data, and make decisions. At the time of testing the system performance will be programmed with several menu selections between numbers 1, 2, 4, and 5 which have their respective functions. In sending the data, it will be tested at a certain distance using 2 Nodes, namely 1 Transmitter Node as the sender of the measurement results, and 1 Receiver Node to receive the measurement results.